Faktor Yang Berhubungan Dengan Kesadaran Pekerja Melaporkan Kejadian Nyaris Celaka Di PT. Charoen Pokphand Makassar - Fausia, Fadya; A. Rizki Amelia; Fatmah Afrianty Gobel (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
According to the statistical data provided by the Ministry of Manpower and Transmigration (Kemenakertrans), 99,491 near-miss incidents were recorded in Indonesia during 2011, accounting for 40.45% of all reported events. The framework established by Bird and Germain (1990) highlights a significant correlation between accident rates, indicating that an alarming ratio exists. For approximately every 300 near misses, 29 minor or one serious or fatal injury can occur. Near-miss incidents signify critical opportunities to address potential workplace hazards, making it essential for all employees to recognize the importance of reporting these events, no matter how insignificant they may seem, to mitigate the risk of workplace accidents. This study aims to explore the relationship between education level and workers' awareness of the necessity to report near-miss incidents. The research adopted a cross-sectional approach using quantitative methods. The study population consisted of 74 individuals, with sampling conducted through Probability Sampling using a Simple Random Sampling technique. Data was gathered via a comprehensive questionnaire, and both univariate and bivariate analyses were carried out using the chi-square test. The findings suggest no significant relationship exists between education level and the awareness of reporting near misses.